Pengetahuan Perempuan Pesisir terhadap Blue Economy di Desa Puger Kulon Kabupaten Jember - Arindra Dewi (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Coastal women in Puger Kulon Village play an active role in the marine economy as fish traders and financiers (pengambe’). However, their economic activities have not been accompanied by adequate awareness of environmental responsibility, especially related to the concept of the blue economy. That the study emphasized on how coastal women's knowledge of the blue economy. The blue economy is a sustainable economic approach that emphasizes the efficient use of marine resources without damaging the ecosystem. This study aims to describe the knowledge of coastal women about the concept of the blue economy in Puger Kulon Village, Jember Regency. This study use a descriptive qualitative approach with purposive area to determine the location of the study and purposive sampling to select informants. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model and validated through triangulation of sources, techniques, and time. The results of the study indicate that coastal women still do not have knowledge about the principles of the blue economy, especially related to awareness of cleanliness in the TPI environment. In terms of attention, retention, motor reproduction, and motivation, they have not developed a collective awareness of environmental sustainability. Their understanding and application of blue economy indicators such as natural efficiency, zero waste, social awareness, and multiple revenue have also not been fully implemented. In conclusion, although coastal women have an important role in local economic activities, their low environmental literacy is a challenge in achieving environmentally friendly economic practices. Therefore, continuous education and support are essential to increase ecological awareness among coastal women.
Entry oleh Arif 2026 Maret 16
Keywords: Coastal Women; Blue Economy; Knowledge